A new species of Dendroleon Brauer, 1866 (Neuroptera, Myrmeleontidae) from China - Zhan, Qingbin; Wang, Zhiliang; Ábrahám, Levente; Wang, Xinli (Zootaxa, 2012)
A new species of the genus Dendroleon (Dendroleon falcatus Zhan & Wang sp. nov.) is described from China. This new species can be distinguished from other Dendroleon species by the following characters: the significantly larger size, the long abdomen in males, and the particular wing shape and markings. Dendroleon javanus Banks, 1914 was previously reported in China based on a misidentification; the Chinese specimens are actually Bullanga florida (Navás, 1913). An identification key and distribution map are provided for Dendroleon species recorded from China.